(untitled) (Revista Argentina de Musicología, 2022)
Phonographic production is represented as a mode of creative expression that is not limited to the simple capture of sound, but transforms it based on a set of decisions that are debated between artistic intuition and technological mediation. The study of the sound parameters of a phonographic production entails an in-depth analysis of the textures that are formed within the multitrack project of a tape recorder or DAW software. The tactility of the sound, in the words of Allan F. Moore (2012), in a recording depends on multiple factors that combine musical and technical parameters, personalized in the action of the music producer. The article reviews the main approaches that have been made to the study of musical production from musicology, proposing a categorization of the different analysis parameters and the difficulties involved in facing this object of study.